2020
DOI: 10.1096/fj.201902222r
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes white adipocytes browning and improves metabolic disorders in Sirt1‐dependent manner in mice

Abstract: Obesity has become an epidemic concern in modern society. The chronic obesity is associated with metabolic disorders, such as hyperglycemia, hyperlipidemia, fatty liver, and cadiovascular disease, which cause high risk for mortality. The novel potential strategy to overcome obesity is to “burn out” the extra fat via “browning” of the white adipose tissues. The phytochemical resveratrol (Res) has attracted substantial attention due to its powerful amelioratory effects in metabolic diseases. However, how Res reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
(93 reference statements)
1
24
0
2
Order By: Relevance
“…[48] It has been reported that CR and SIRT1 activation promote the recruitment of brown adipocytes within WAT, an effect that has been associated with improved glucose homeostasis. [49,50] Consistent with these reports, we found a remarkable induction of brown adipocyte-specific genes (i.e., Ucp1, Adrb3, or Cidea) in subcutaneous WAT of CR mice, whereas the effects of SIRT1 overexpression on the expression of these genes was very marginal or inexistent. Importantly, regardless of the effects on the mRNA levels of brown adipocyte-specific genes, we did not find any detectable UCP1 protein in WAT of CR and Sirt1-Tg mice, suggesting that browning of WAT was negligible.…”
Section: Discussionsupporting
confidence: 89%
“…[48] It has been reported that CR and SIRT1 activation promote the recruitment of brown adipocytes within WAT, an effect that has been associated with improved glucose homeostasis. [49,50] Consistent with these reports, we found a remarkable induction of brown adipocyte-specific genes (i.e., Ucp1, Adrb3, or Cidea) in subcutaneous WAT of CR mice, whereas the effects of SIRT1 overexpression on the expression of these genes was very marginal or inexistent. Importantly, regardless of the effects on the mRNA levels of brown adipocyte-specific genes, we did not find any detectable UCP1 protein in WAT of CR and Sirt1-Tg mice, suggesting that browning of WAT was negligible.…”
Section: Discussionsupporting
confidence: 89%
“…Transmission electron microscopy showed that 3T3-L1 cells treated with BBR exhibited the characteristics of brown-like adipocytes with increased mitochondrial density and smaller lipid droplets (Figure 4 B). Previous studies have demonstrated that SIRT1 played an important role in energy metabolism and remodeling of adipose tissue 21 , 44 , 45 . We next elucidated whether SIRT1 is necessary for BBR to regulate the remodeling of adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Bars represent the mean ± SD. *P < 0.05 of cellular biochemical processes (Li et al, 2020;Liu et al, 2020;Wu et al, 2018;Zhang, Bi, et al, 2019). Mounting evidence indicated that SIRT1 could enhance the expression and transcriptional activity of Nrf2 to exert potent anti-oxidant effects (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 might be involved in the mechanisms by which astaxanthin modulates Nrf2/Prx2/ASK1/p38 signalling after traumatic brain injury. SIRT1 is a type of histone deacetylase that regulates a variety of cellular biochemical processes (Li et al, 2020; Liu et al, 2020; Wu et al, 2018; Zhang, Bi, et al, 2019). Mounting evidence indicated that SIRT1 could enhance the expression and transcriptional activity of Nrf2 to exert potent anti‐oxidant effects (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%